Physeter macrocephalus Linnaeus 1758 - Thu, Aye Myat; Lwin, Ye Htet; Quan, Rui-Chang (Zenodo, 2024)
360. Physeter macrocephalus Linnaeus, 1758 Common name: Sperm Whale Myanmar name: Distribution: Antarctic and cold-temperate waters (Northern hemisphere) to tropical waters. In Myanmar, recorded in the offshore waters of Bay of Bengal (Parnum 2019). Remarks: This species is listed as vulnerable by the IUCN and a completely protected species of Myanmar. Published as part of Thu, Aye Myat, Lwin, Ye Htet & Quan, Rui-Chang, 2024, Mammals of Myanmar: an annotated checklist, pp. 147-197 in Mammalia (Warsaw, Poland) (Warsaw, Poland) 88 (3) on pages 191-192, DOI:10.1515/mammalia-2023-0098, http://zenodo.org/record/13913939